Evaluation of colours to oviposition of Ceratitis capitata (Diptera, Tephritidae) in Argentina - Suárez, Lorena (2007)
Ceratitis capitata is one of the most important fruit plagues of the world and it is the most abundant and widely distributed fruit fly in Argentina. To develop an egg trap over artificial substrate would be a useful tool to monitoring gravid female. The objective of this study was to evaluate the attraction capacity of different colours to egg laying over agar spheres of C. capitata in laboratory conditions. Five colours: yellow, red, green, black and without colour were proved. The red and black spheres were more attractive, showing significant statistics differences, than green, yellow and without colour. In the lab, the major attraction of dark colours to support the hypothesis that the strong contrast against the background would increase their attraction.